Cerebral Aneurysms: A Rare Feature of Behçet's Disease—A Case Report and Review of the Literature - Samia Younes; Yosra Cherif; Narjes Mokni; Olfa Berriche; Baha Zantour; Amel Boughammoura; Mahbouba Frih-Ayed; Saida Jerbi; Mohamed Habib Sfar (Case Reports in Neurological Medicine)
Behçet's disease (BD) is a multisystem vascular inflammatory disease with several clinical manifestations. Intracranial aneurysms are an extremely rare but nevertheless severe complication of BD. We report a case of a 44-year-old man. The diagnosis of BD was made based on the presence of recurrent oral aphthous ulcers and positive human leukocyte antigen (HLA-) B51 in the absence of evidence of other diseases. MRI showed an ancient ischemic right capsulolenticular lesion, subacute white matter hypersignals of the left capsule lenticular region, and multiple arterial aneurysms. The patient underwent two-month systemic high-dose corticosteroids and immunosuppressive therapy associated with severe neurological deficiency upon admission and severe impairment upon discharge. A thorough review of the literature showed 20 case reports of intracranial aneurysms in BD.